Contemporary orthodontics - Proffit, William R. ; Fields, Henry W. (Mosby, 2020)
Now in full color, Contemporary Orthodontics, 5th Edition is a practical resource with a long tradition of excellence. Line drawings and more than 1,000 new color images illustrate concepts more clearly than ever. This book includes detailed information on diagnosis, treatment planning concepts, related problems or controversies, and current treatment procedures, including the role of orthodontics in comprehensive treatment of patients with multiple problems.